Diasporic Knowledges in Central Asia: (Re)membering in Jeong - Olga Mun ((An)Archive: Childhood, Memory, and the Cold War, 2024)
This is a childhood memory produced as part of the Reconnect/Recollect project discussed in the introduction to this book.